2023
DOI: 10.1002/adfm.202300109
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Engineering Toward Harvesting the Bright Deep‐Blue‐Light Emission in Y‐based Metal‐Organic Frameworks

Abstract: The emergence of metal‐organic frameworks (MOFs) provides a new platform of low‐cost and color‐saturated blue light‐emitting diodes ideal for display and solid‐state lighting applications. However, numerous established MOFs still exhibit weak deep‐blue‐light emission (<450 nm) owing to low energy/charge transfer efficiency. Here a pressure‐treated strategy to greatly enhance photoluminescence performance of deep‐blue light‐emitting Y(BTC)(H2O)6 (H3BTC: benzene‐1,3,5‐tricarboxylic acid) is reported. Pressure‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In addition, the same group found that a nonemission MOF-2 and YðBTCÞðH 2 OÞ 6 also exhibit pressureresponsive photoluminescence. 127,128 Moggach et al also reported pressure-induced photoluminescence of Hf-peb MOF due to the linker rotation. 129…”
Section: Pressure-responsivementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the same group found that a nonemission MOF-2 and YðBTCÞðH 2 OÞ 6 also exhibit pressureresponsive photoluminescence. 127,128 Moggach et al also reported pressure-induced photoluminescence of Hf-peb MOF due to the linker rotation. 129…”
Section: Pressure-responsivementioning
confidence: 98%
“…Further research suggests that the mechanism of this pressure-responsive MOF can be attributed to the enhanced hydrogen bonds lock causing enhanced intersystem crossing to effectively drive ligand-to-metal energy transfer. In addition, the same group found that a non-emission MOF-2 and Y(BTC)(normalH2Ofalse)6 also exhibit pressure-responsive photoluminescence 127 , 128 . Moggach et al.…”
Section: Stimuli-responsive Photonic Mofsmentioning
confidence: 99%
“…52 On the other hand, the yttriumbased MOF, [Y(BTC)(H 2 O) 6 ], has shown enhanced blue emission with an increase in the PLQY from 2.8% to 75.0% upon applying increasing amounts of pressure, followed by the release of pressure. 55 After a series of crystal structure analyses, the amplified PLQY values were attributed to stronger hydrogen-bonding interactions at a higher pressure, which would, in turn, lead to enhanced planarization of the structure composed of the yttrium center and the three benzene rings connected to it, allowing more conjugation and charge transport. 55 Another example is OX-2, which is composed of BDC linkers (H 2 BDC = 1,4-benzenedicarboxylic acid) bound to silver ions (Ag + ).…”
Section: Metal−organic Framework (Mofs)mentioning
confidence: 99%
“…55 After a series of crystal structure analyses, the amplified PLQY values were attributed to stronger hydrogen-bonding interactions at a higher pressure, which would, in turn, lead to enhanced planarization of the structure composed of the yttrium center and the three benzene rings connected to it, allowing more conjugation and charge transport. 55 Another example is OX-2, which is composed of BDC linkers (H 2 BDC = 1,4-benzenedicarboxylic acid) bound to silver ions (Ag + ). It could be synthesized in different solvents to give isostructural OX-2 w (water), OX-2 m (methanol), and OX-2 DMF (N,N-dimethylformamide), which only differ from each other by the encapsulated solvent molecules.…”
Section: Metal−organic Framework (Mofs)mentioning
confidence: 99%
See 1 more Smart Citation